Selecting Suitable Functionals and Basis Sets on the Study Structural and Adsorption of Urea-Kaolinite System Using Cluster Method - Nur Najwa-Alyani Mohd Nabil; Lee Sin Ang (Indonesian Journal of Chemistry, 2022)
Kaolinite is an essential mineral with numerous applications across many sectors. One of them is in the agricultural industry, in which it is a crucial component in the method of controlled-release fertilizer. This manuscript reports the use of different functionals and basis sets on the structural and electronic properties of kaolinite's surface, intending to find reliable methods among those tested. Four different functionals, B3LYP, CAM-B3LYP, M06-2X, TPSSTPSS, complemented with various basis sets, were used in this study. The results show that TPSSTPSS complement with 6-311G** provides good agreement with previous research and experimental results among different functionals and basis sets used. The quantitative analysis was done to optimize the kaolinite molecule. Selected extrema points were used to place the urea molecule for the interaction of urea-kaolinite studies. The urea's interaction with kaolinite was reported at a different interaction site in the gas phase and different orientations of the urea molecule. Urea molecule was optimized above the Al–O and Si–O surfaces with their energy difference calculated. Our results showed that both surfaces act as promising adsorbents among the different orientations of the urea on both the Al–O and Si–O surfaces. However, Al–O, and Si–O had another preferable interaction site to the urea molecules.